Optimized protocols for protoplast isolation, transfection, and regeneration in the Solanum genus for the CRISPR/Cas-mediated transgene-free genome editing - So Hee Yang; Suk Weon Kim; Sujin Lee; Yeonjong Koo (Applied Biological Chemistry, 2024)
Abstract The Solanaceae family includes the largest flowering crops such as tomatoes, potatoes, and eggplants. Consumer demand has led to massive development of plants in the Solanum genus, and many different Solanum varieties are now available on the market. The recent advances in Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein 9 (Cas9)-based genome editing have allowed laboratories and smaller crop production companies to utilize the technology in various crops. The traditional transformation method in crops involves the use of Agrobacterium, which is considered the most efficient method for introducing exogenous genetic materials in target plants. The Agrobacterium-mediated transformation method has been also established in the Solanaceae family, enabling CRISPR/Cas-based genome editing in crops like tomatoes, potatoes, and eggplants. However, the Agrobacterium-mediated approach inevitably accompanies the insertion of exogenous DNA into the plant genome and often causes the formation of chimera that require further propagation steps. Alternatively, the CRISPR/Cas components can be introduced into protoplasts in the form of DNA for transient expression or a mixture of protein and RNA to avoid genomic insertion of foreign materials. The protoplast transformation approach involves processes including protoplast preparation, transfection, and regeneration, which require a comprehensive understanding and greater technical mastery of the tissue culture phase. Here we highlight the current research advances in protoplast transformation and discuss how to optimize the procedures of protoplast isolation, transfection, and regeneration for efficient and reproducible CRISPR/Cas-based genome editing in the genus Solanum.